Accuracy of Genomic Selection for Important Economic Traits of Cashmere and Meat Goats Assessed by Simulation Study - Yan, Xiaochun; Zhang, Tao; Liu, Lichun; Yu, Yongsheng; Yang, Guang; Han, Yaqian; Gong, Gao; Wang, Fenghong; Zhang, Lei; Liu, Hongfu; Li, Wenze; Yan, Xiaomin; et al. (Frontiers in Veterinary Science, 2022)
Genomic selection in plants and animals has become a standard tool for breeding by advantage of high accuracy and short generation intervals. Implementation of this technology is hindered by the high cost of genotyping and other factors. The aim of study is to determine optional marker density panel, reference population size for using genomic selection of goats, and speculate the number of QTLs that affected the important economic traits of goats. Besides, the effect of bulls size in reference population on accuracy of GEBV was discussed. Based on the previous genetic evaluation results of Inner Mongolia White Cashmere goats, the live body weight (LBW, h2=0.11) and fiber diameter (FD, h2=0.34) were chosen to perform genomic selection in this study. Reasonable genome parameters and generation transmission processes were set, phenotypic and genotype data of the two traits were simulated. Then, different sizes of reference population and validation population were selected from progeny. The genomic estimated breeding values (GEBV) were obtained by five methods including GBLUP, BayesA, BayesB, Bayesian Ridge Regression, Bayesian LASSO. The correlation coefficient between the predicted and realized phenotype from simulation was calculated and used as a measure of the accuracy of GEBV in each trait. The results showed that the medium marker density panel (45K) could be used for genomic selection in goats, which can ensure the accuracy of GEBV. The reference population size of 1500 can obtain greater genetic progress in genomic selection for fiber diameter and live body weight in goats by comparing with the population size below this level. The accuracy of GEBV for live body weight and fiber diameter will be better when the number of QTLs were 100 and 50, respectively. Additionally, it was discovered that the accuracy of GEBV is good when the bull size was up to 200. Meanwhile, it was found that accuracy of GEBV in medium heritability trait (FD) was higher than that in low heritability trait (LBW). These will provide theoretical guidance for genome selection in goats by using real data.